In-situ intercalation of NiFe LDH materials: An efficient approach to improve electrocatalytic activity and stability for water splitting - Li, Xiumin; Hao, Xiaogang; Wang, Zhongde; Abudula, Abuliti; Guan, Guoqing (Journal of power sources, 2017)
Intercalation and exfoliation are effective approaches for enlarging the interlayer distance and increasing ion exchange capacity of layered materials. Here, an in-situ intercalation method is demonstrated to expand the inter-layer spacing of electrodeposited NiFe Layered Double Hydroxides (LDH) electrodes. Compared with traditional electrode fabrication method, in which intercalation/exfoliation of LDH powders is performed first followed by coating it on substrate, better interface connection and stability are maintained in the present method. It is found that the inter-layer distance of NiFe LDH material can be increased from 7.8 to 9.5 Å by immersing the electrode in formamide at 80 °C for 3 h, and the required overpotential of oxygen evolution reaction (OER) for sustaining 10 mA cm−2 current density is reduced from 256 to 210 mV. Moreover, with the assistance of ultrasound treatment, the required intercalation time is reduced drastically and the overpotential@10 mA cm−2 current density is further decreased to 203 mV. [Display omitted] •NiFe LDH electrodes are synthesized by unipolar pulse electro-deposition method.•An in-situ intercalation method is performed over electrodeposited NiFe LDH electrode.•Effect of ultrasound and temperature on the property of intercalated electrodes is studied.•The electrode shows an extremely low overpotential of 203 mV@10 mA cm−2.